Diferencias de los valores de eficacia en igualdad numérica entre equipos perdedores en waterpolo masculino y femenino - Argudo Iturriaga, Francisco Manuel; García Marín, Pablo; Alonso Roque, José Ignacio; Ruiz Lara, Encarna (KRONOS, 2007)
This research job has tried two goals: to fit accuracy values in microsituations of play situational framework in numerical equality with or without posesión of the ball and to analize the relaction among the accuracy values in losing teams at the end of the match in both sexes. For empirical part all Barcelona 2003 water polo X World Championship matches were filmed. After observation and analysis, the use of coefficients was valued by means of accuracy in all microsituations of play mentioned, obtaining some values of accuracy. Differences among sexes in the coefficientes were detected: blocked shots made (.000), blocked shots against (.004), possibility of shots with possession (.008), definition of shots with possession (.012) and resolution of shots with possession (.018); taking p<.05 as a reference value. To conclude, we can say that five fourteen proposed coefficients of accuracy to evaluate the microsituations of play in numerical equality with or without possession of the ball in water polo show significant difference among sexes in losing teams at the end of the match.